Psychopedagogical guidance strategy for educational quality: a claim in the training of athletes - Danaysi Alvarez Cobas; Tania Yakelyn Cala Peguero; Mayra Ordaz Hernández (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: in the training process of student- athletes, conceived as subjects endowed with high capacities, the harmonization of teaching with the practice of high competition sports represents a challenge for educational institutions. So, the introduction of innovative resources that contribute to the correct development of this assignment constitutes a claim. Objective: to design a series of psychopedagogical guidance actions for the comprehensive training of Taekwondo student-athletes of the "Ormani Arenado" Sport Initiation School (Eide in Spanish), so that they can harmonize sports practice with teaching activity. Materials and methods: the methodology followed is based on a qualitative research perspective, where the descriptive and exploratory methods were fundamental in the diagnosis of the current conditions of the psychopedagogical guidance process. The analysis of documents, semi-structured interviews and the survey were th fundamental methods used to collect relevant information for the design of the proposed activities. Results: the study derives the need to implement actions that improve the process of psychopedagogical guidance to student-athletes, so that they contribute to the optimal harmonization between sports and academic activity. Conclusions: the main contribution of the proposed strategy is the recognition of the need to achieve coordinated work between teachers, coaches, psychologists, educational psychologists and the rest of those involved in the comprehensive training of student -athletes, in a process where the latter necessarily have to assume an active role.